Grinding Synthesis of Schiff Bases Combined with Infrared Irradiation - Tong, Jian-Ying; Sun, Na-Bo; Wu, Hong-Ke (Asian Journal of Chemistry, 2013)
Solid-phase synthesis combined with infrared irradiation promoted the formation of a series of Schiff bases in the condensation reaction between substituted benzaldehydes and anilines, in the solvent free. Benzaldehydes and anilines, containing either electron withdrawing or electron-releasing groups, were evaluated their substituent effect on the formation of the Schiff bases. Moreover, this new procedure is environmentally benign because no solvent was employed in the transformations.